Adolescent Substance Use & Psychopathology: Interactive Effects of Cortisol Reactivity and Emotion Regulation - Poon, Jennifer A. (Cognit Ther Res, 2015)
How are emotional processes associated with the increased rates of substance use and psychological disorders commonly observed during adolescence? An index of emotion-related physiological arousal—cortisol reactivity—and subjective emotion regulation have both been independently linked to substance use and psychological difficulties among youth. The current study (N = 134 adolescents) sought to elucidate the interactive effects of cortisol reactivity following a stressful parent–child interaction task and self-reported emotion regulation ability on adolescents’ substance use and externalizing and internalizing behavior problems. Results revealed that adolescents with low levels of cortisol reactivity and high emotion regulation difficulties were more likely to use substances, and also had the highest parent-reported symptoms of oppositional defiant disorder. With respect to internalizing symptoms, high emotion-related physiological reactivity coupled with high emotion regulation difficulties were associated with higher self-reported major depression symptoms among youth. Findings reveal that different profiles of HPA axis arousal and emotion regulation are associated with substance use and symptoms of psychopathology among adolescents.